Sexual Size Dimorphism in Relation to Age and Growth in Hypsiboas cordobae (Anura: Hylidae) from Córdoba, Argentina - Otero, Manuel Alejandro (2017)
Most anurans exhibit sexual size dimorphism (SSD). This morphological variation between the sexes may be attributed to different ages at maturity, growth rate, or longevity. We present the first data on age structure and growth pattern of Hypsiboas cordobae using skeletochronology, and analyze SSD considering age-specific differences in body size based on 71 individuals. Snout-vent length (SVL) and body mass (BM) were significantly different between the sexes. Females were larger and heavier than males, but mean age between adult males and females was not significantly different. Minimum age at sexual maturity, longevity, and potential reproductive lifespan did not differ between the sexes. Female SVL and BM at sexual maturity were significantly larger than those of males. ANCOVA revealed significant sexual differences in body size and weight. The sexual dimorphism index in body size was 0.0679 (SVL) and 0.3621 (BM). Growth curves using the von Bertalanffy model showed a similar profile in both sexes, but the growth coefficient was higher in males. Age determination and the von Bertalanffy growth model for H. cordobae allowed us to determine SSD and our results may provide baseline data on the demography of H. cordobae.